(untitled) (Journal of Medical & Health Sciences Review, 2025)
Abstract: Background: Medication errors (MEs) present significant risks to patient safety worldwide, necessitating vigilant reporting and awareness among healthcare professionals, particularly nurses in critical care. In Pakistan, where healthcare systems face unique challenges, understanding nurses’ awareness and practices regarding MEs is essential for improving patient safety outcomes. Aim: This study aimed to assess nurses’ knowledge and perceptions of medication error reporting practices in critical care settings in Punjab, Pakistan. Methodology: A cross-sectional survey was conducted from February 5 to February 19, 2024, using a structured questionnaire distributed via online platforms. Convenience sampling included nurses from diverse healthcare settings. Quantitative data were analyzed using SPSS version 23, with ethical considerations ensuring confidentiality and voluntary participation. Results: Among the respondents, 67% lacked knowledge of hospital policies on MEs, and 23.3% misconceived near-miss incidents as errors. While 77% recognized the importance of reporting MEs regardless of harm, 41.7% feared disciplinary action, and 68% cited usability concerns with reporting systems. Despite these gaps, 83.9% demonstrated the ability to identify reportable MEs, and 92% agreed on reporting all adverse drug events. Conclusion: The findings highlight critical knowledge gaps, misconceptions, and barriers to reporting MEs among nurses. Addressing these challenges through targeted education, training, and fostering a supportive reporting culture is essential to enhance patient safety in Punjab’s critical care settings. Future research should focus on developing and evaluating interventions to improve reporting practices.